Respon Beberapa Varietas Padi Ketan terhadap Cekaman Kekeringan Response of Some Varieties of Glutinous Rice to Drought - noviyanti eka maudina; Sunawan Sunawan; Mahayu Woro Lestari (AGRONISMA, 2021)
Drought is a problem that is very influential in the field of agriculture, such as a decrease in food production which will disrupt food security and national economic stability. Rice plants are very sensitive to drought stress. The response of rice plants to drought stress is highly dependent on the severity of the drought, the growing phase of the drought, and the genotype. This study aims to determine the effect of drought stress on the yield of several varieties of glutinous rice. This research was conducted from October 2020 to March 2021 in green house Agriculture Faculty, University of Islam Malang, Dinoyo Village, Lowokwaru District, Malang City, East Java. Using a Divided Plot Design (RPT) compiled with a 4-factor Randomized Block Design (RAK). The first factor is the type of glutinous rice plant variety (V), which consists of 4 levels, namely: V1 = variety Grendel, V2 = variety Siem, V3 = variety Wuluh and V4 = variety Putri Pym 20.Â  While the second factor is drought which consists of 4 types, namely: C0 = no drought, C1 = drought 1 week after flowering, C2 = drought 2 week after flowering and C3 = drought 3 week after flowering. Statistical test of ANOVA analysis of variance and 5% BNT follow-up test. The results of analysis of variance (ANOVA) showed that in general, the combination of glutinous rice varieties with drought did not interact with plant growth and yield parameters. However, at the parameters of panicle length there were interactions. Separately, the treatment of glutinous rice variety had a significant effect only on the parameters of plant growth and yield. Furthermore, the treatment of drought gave a significant effect on the parameter of stem water level. The best response was generally shown by the Putri Pym 20 variety of glutinous rice.